Singing for people with aphasia (SPA): results of a pilot feasibility randomised controlled trial of a group singing intervention investigating acceptability and feasibility. Issue 1 (13th January 2021) - Tarrant, Mark; Carter, Mary; Dean, Sarah Gerard; Taylor, Rod; Warren, Fiona C; Spencer, Anne; Adamson, Jane; Landa, Paolo; Code, Chris; Backhouse, Amy; Lamont, Ruth A; Calitri, Raff
Abstract : Objectives: Pilot feasibility randomised controlled trial (RCT) for the singing groups for people with aphasia (SPA) intervention to assess: (1) the acceptability and feasibility of participant recruitment, randomisation and allocation concealment; (2) retention rates; (3) variance of continuous outcome measures; (4) outcome measure completion and participant burden; (5) fidelity of intervention delivery; (6) SPA intervention costs; (7) acceptability and feasibility of trial and intervention to participants and others involved. Design: A two-group, assessor-blinded, randomised controlled external pilot trial with parallel mixed methods process evaluation and economic evaluation. Setting: Three community-based cohorts in the South-West of England. Participants: Eligible participants with post-stroke aphasia were randomised 1:1 to SPA or control. Intervention: The manualised SPA intervention was delivered over 10 weekly singing group sessions, led by a music facilitator and assisted by an individual with post-stroke aphasia. The intervention was developed using the Information-Motivation-Behavioural skills model of behaviour change and targeted psychosocial outcomes. Control and intervention participants all received an aphasia information resource pack. Outcome measures: Collected at baseline, 3 and 6 months post-randomisation, candidate primary outcomes were measured (well-being, quality of life and social participation) as well as additional clinical outcomes. Feasibility, acceptability and process outcomes included recruitment and retention rates, and measurement burden; and trial experiences were explored in qualitative interviews. Results: Of 87 individuals screened, 42 participants were recruited and 41 randomised (SPA=20, control=21); 36 participants (SPA=17, control=19) completed 3-month follow-up, 34 (SPA=18, control=16) completed 6-month follow-up. Recruitment and retention (83%) were acceptable for a definitive RCT, and participants did not find the study requirements burdensome. High fidelity of the intervention delivery was shown by high attendance rates and facilitator adherence to the manual, and participants found SPA acceptable. Sample size estimates for a definitive RCT and primary/secondary outcomes were identified. Conclusions: The SPA pilot RCT fulfilled its objectives, and demonstrated that a definitive RCT of the intervention would be both feasible and acceptable. Trial registration number: NCT03076736 .